Diagnóstico energético de las bombas centrifugas de 1500 hp del bloque 16 de repsol en el año 2013. Propuesta de un esquema de gestión continua de la eficiencia energética para optimizar la producción. - Veintimilla Bautista, Raúl (2017)
The objective of this project is the consumption of the 1500 HP pumps of Block 16 of Repsol through a diagnosis that allows energy optimization. The need for this study lies in the gradual increase of the water of the formation that extracted together with the crude oil and the problem of the reinjection of this water may rise, the reason why the energy analysis of the reinjection system used. The water pumping process in the Block 16 of Repsol has a high demand for electricity that is around 98 MW. This is due to a liquid extraction of 900.00 barrels. Centrifugal water reinjection pumps for the largest energy consumers within the entire Block 16 of Repsol. This study does in the North Production Facilities (NPF) whose object of study refers to three pumps of high pressure of 1500 Hp the pump of Capiron A18:M1 that re-injects 25% of the total water, followed by the Bogi 1 UWD whit 19% and finally the Tivacunno A2WD with 18%. The elaboration of study always starts from the visual exploration and responded by the information provided by operators and technicians of the plant, who are the first to implement the new plan of operational measures and maintenance of Repsol.